Democratic transition and constitutional justice: post Reformasi Constitutional Adjudication in Indonesia - Satriawan, Iwan; Mokhtar, Khairil Azmin (IIUM Press, International Islamic University Malaysia, 2020)
The fall of New Order Regime under President Suharto saw the emergence of Reformasi (Reformation) and the beginning of various institutional and governmental changes done in the pursuit of democracy in Indonesia. Constitutional justice is fundamental to the success of democratic transition in the country. One of the results democratic reform and constitutional changes after Reformasi in 1998 is the establishment of the Constitutional Court of the Republic of Indonesia.